Suicidality in primary care patients who present with sadness and anhedonia - Moreno-Küstner, Berta (2017)
Background: Sadness and anhedonia (loss of interest in activities) are central symptoms of major depression. However, not all people with these symptoms meet diagnostic criteria for major depression. We aimed to assess the importance of suicidality in the outcomes for primary care patients who present with sadness and anhedonia. Method: Cohort study of 2,599 unselected primary care attenders in six European countries followed up at 6 and 12 months. Results: 1) In patients with sadness and/or anhedonia who were not depressed at entry to the study, suicide plans (OR = 3.05; 95 % CI = 1.50-6.24; p = 0.0022) and suicide attempts (OR = 9.08; 95 % CI = 2.57-32.03; p = 0.0006) were significant predictors of developing new onset depression at 6 or 12 months. 2) In patients with sadness and/or anhedonia who met CIDI criteria for major depression at entry, suicidal ideation (OR = 2.93; 95 % CI = 1.70-5.07; p = 0.0001), suicide plans (OR = 3.70; 95 % CI = 2.08-6.57; p < 0.0001), and suicide attempts (OR = 3.33; 95 % CI = 1.47-7.54; p = 0.0040) were significant predictors of persistent depression at 6 or 12 months. Conclusions: Three questions on suicidality could help primary care professionals to assess such patients more closely without necessarily establishing whether they meet criteria for major depression.